The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/celc.202001475
|View full text |Cite
|
Sign up to set email alerts
|

NiFeMo Nanoparticles Encapsulated within Nitrogen‐Doped Reduced Graphene Oxide as Bifunctional Electrocatalysts for Zinc‐Air Batteries

Abstract: Rechargeable metal‐air batteries (MABs) have emerged as promising candidates for portable energy storage technologies because of their favorable energy/power density, safety, and cost‐effectiveness. However, the lack of advanced bifunctional electrocatalysts for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) restricts the commercial realization of rechargeable MABs. Herein, we developed a facile fabrication route to prepare N‐doped graphene oxide encapsulating nanoparticles of a ternar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…21 A Cu-nanowire core–cell structure was used to grow NiFeMo by electrodeposition; it required 1.82 V for overall water splitting, 29 whereas NiFeMo@N-rGO exhibits a high OER overpotential of 330 mV. 30 Amorphous NiFeMo outperforms its crystalline structure for the OER catalysis, which undergoes rapid self-reconstruction. 24 Moreover, NiFeMO has not been investigated at industry-relevant current densities, which plays a key role in the industrialisation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 A Cu-nanowire core–cell structure was used to grow NiFeMo by electrodeposition; it required 1.82 V for overall water splitting, 29 whereas NiFeMo@N-rGO exhibits a high OER overpotential of 330 mV. 30 Amorphous NiFeMo outperforms its crystalline structure for the OER catalysis, which undergoes rapid self-reconstruction. 24 Moreover, NiFeMO has not been investigated at industry-relevant current densities, which plays a key role in the industrialisation process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, NiFeMO has been widely investigated, and it has proved to be a promising candidate for industrial-relevant hydrogen production due to its excellent OER activity and scientic signicance. 21,23,24,[26][27][28][29][30][31][32][33] A careful investigation of the literature survey (Table S1, ESI †) indicated that the enhanced catalytic performance is either due to the improved quantity and quality of the active sites through compositions or the design of the nanostructures. NiFeMO is expected to be a bifunctional catalyst for overall water splitting; however, the reaction mechanism of the enhanced catalytic activity for which most active compositions is still not clearly presented.…”
Section: Introductionmentioning
confidence: 99%